PENERAPAN METODE INKUIRI DALAM PENINGKATAN PRESTASI BELAJAR IPAS KELAS IV SEMESTER 1 SDN 3 KARANGASEM KECAMATAN WIROSARI KABUPATEN GROBOGAN - Retno Murtianingrum, Puji (Universitas Muria Kudus, 2025)
The purpose of this study was to describe the application of the inquiry method in improving the learning outcomes of Class IV Science Students Semester 1 SDN 3 Karangasem, Wirosari District, Grobogan Regency, Academic Year 2023/2024. This research method is a classroom action research with a research design referring to the Kemmis Mc. Taggart Model which is divided into 4 stages, namely: planning, implementation of actions, observation, and reflection. The types of data used are quantitative data and qualitative data. This implementation was carried out in two cycles and two meetings each. The subjects of this study were class IV 1 students of SDN 3 Karangasem. The research instruments were the results of the Science assessment, observation, interviews, and documentation. Data collection techniques include interviews, observations, documentation and test techniques. The results of the study showed that by using the inquiry method there was an increase in the learning outcomes of Science Students in Chapter 2 of the Form of Matter and Its Changes. In cycle I, the average score reached 54.34, which was categorized as still unsuccessful, while in cycle II the average score reached 78.26.